2023
DOI: 10.3390/diagnostics13101707
|View full text |Cite
|
Sign up to set email alerts
|

Direct Anthropometry Overestimates Cranial Asymmetry—3D Digital Photography Proves to Be a Reliable Alternative

Felix Nieberle,
Steffen Spoerl,
Lisa-Marie Lottner
et al.

Abstract: This study compared manual and digital measurements of plagiocephaly and brachycephaly in infants and evaluated whether three-dimensional (3D) digital photography measurements can be used as a superior alternative in everyday clinical practice. A total of 111 infants (103 with plagiocephalus and 8 with brachycephalus) were included in this study. Head circumference, length and width, bilateral diagonal head length, and bilateral distance from the glabella to the tragus were assessed by manual assessment (tape … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
(114 reference statements)
0
2
0
Order By: Relevance
“…This minimizes movement artifacts, making it ideal for data acquisition, especially for infants. While validation tests of the scanner have been conducted on a mannequin head, 14 healthy adults, 15 patients with cleft lips or palates, 16 17 and infant's head, 18 it has not yet received approval for use as a medical device by the Pharmaceuticals and Medical Devices Agency in Japan. The VECTRA-M5 360° 3D scanner was calibrated daily following the manufacturer's instructions to ensure the accurate geometric configuration of all cameras.…”
Section: Methodsmentioning
confidence: 99%
“…This minimizes movement artifacts, making it ideal for data acquisition, especially for infants. While validation tests of the scanner have been conducted on a mannequin head, 14 healthy adults, 15 patients with cleft lips or palates, 16 17 and infant's head, 18 it has not yet received approval for use as a medical device by the Pharmaceuticals and Medical Devices Agency in Japan. The VECTRA-M5 360° 3D scanner was calibrated daily following the manufacturer's instructions to ensure the accurate geometric configuration of all cameras.…”
Section: Methodsmentioning
confidence: 99%
“…In a study, Felix Nieberle et al, 17 showed that direct anthropometry overestimates cranial asymmetry, and 3D digital photography proves to be a reliable alternative. In this study, a total of 111 infants (103 with plagiocephaly and 8 with brachycephaly) were included.…”
Section: ) Comparison Between Traditional Head Measurements and Three...mentioning
confidence: 99%